2014
DOI: 10.1007/s11136-014-0702-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health-related quality of life changes after lifestyle intervention in persons at risk of type 2 diabetes mellitus

Abstract: Purpose To assess health-related quality of life (HRQOL) of subjects at risk of type 2 diabetes undergoing lifestyle intervention, and predictors for improved HRQOL. MethodsThe Finnish Diabetes Risk Score was used by general practitioners to identify individuals at risk. Low-intensity interventions with an 18-month follow-up were employed. HRQOL was assessed using the SF-36 at baseline and compared with results from a general Norwegian population survey and further at 6 and 18 months. Simple and multiple linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…In the future preventive programs including lifestyle improvement, weight control and increased physical activity should be established for the large proportion of subjects at risk of DM. We also believe that an individual approach, as exemplified by a small weight loss, eating more fruit, or increasing physical activity in a modest way, will benefit subjects at risk of DM [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the future preventive programs including lifestyle improvement, weight control and increased physical activity should be established for the large proportion of subjects at risk of DM. We also believe that an individual approach, as exemplified by a small weight loss, eating more fruit, or increasing physical activity in a modest way, will benefit subjects at risk of DM [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we found differences in characteristics between organizations (Table 1 ), the potential bias will effect both the intervention and limited group alike, and will not have a large effect on our results (Table 2 ). Second, an attrition bias may occur at the follow-up measurements since those who achieve lifestyle changes might be more willing to do the final assessment than those who do not [ 83 ]. We will try to prevent this by sending personal invitations for final measurements by the OPs and having the OPs stimulate the participant to also fill out the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that we are unable to state with certainty whether weight loss caused improved quality of life. Other variables not assessed in this study could have played a role in quality of life improvements, such as physical activity or type of diet . Furthermore, we cannot generalize these results beyond the clinical trial setting, as differences in quality of life have been observed in varying subgroups of persons with obesity .…”
Section: Discussionmentioning
confidence: 88%